The Evolution of City Form : Evidence from Satellite Data - Lall, Somik V.; Lebrand, Mathilde; Soppelsa, Maria Edisa (World Bank, Washington, DC, 2021)
This paper describes new global evidence—derived from satellite data—for rates and patterns of urban spatial development since 1990 along three margins: horizontal spread (outward extension), infill development (inward additions in the gaps left between earlier structures), and vertical layering (upward construction). The end product of this growth is floor space, the amount and distribution of which are central to understanding how a city becomes livable and sustainable. Over the quarter century between 1990 and 2015, urban built-up area worldwide grew by 30 percent through horizontal spread and infill. While most cities grow through a combination of horizontal spread and infill, the paper provides the first estimates of the relative prominence of each type of expansion at different stages of economic development. In low-income and lower-middle-income countries, 90 percent of urban built-up area expansion occurs as horizontal spread. The study also finds that increasing incomes are a uniquely necessary condition for a rise in floor space per person through vertical layering: the reason is that building tall is capital intensive. The analysis highlights that if a city’s population doubles but incomes stay constant, the city’s floor space per person declines by 40 percent; by contrast, if per capita income doubles but population stays constant, the city’s total floor space per person increases by 29 percent.